2022
DOI: 10.3389/fphar.2022.922337
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Active Ingredients From Chinese Traditional Herb Panax Notoginseng: A Pharmacological Mechanism Review

Abstract: Depression is one of the most common mental illnesses in the world and is highly disabling, lethal, and seriously endangers social stability. The side effects of clinical drugs used to treat depression are obvious, and the onset time is longer. Therefore, there is a great demand for antidepressant drugs with better curative effects, fewer side effects, and shorter onset time. Panax notoginseng, a Chinese herbal medication, has been used to treat depression for thousands of years and shown to have a therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Li et al also surveyed most recent 20 years of research on P . notoginseng for treating depression, which has been shown to have a therapeutic effect on depression [ 62 ].…”
Section: Potential Of P Notoginseng Relieve Post-c...mentioning
confidence: 99%
“…Li et al also surveyed most recent 20 years of research on P . notoginseng for treating depression, which has been shown to have a therapeutic effect on depression [ 62 ].…”
Section: Potential Of P Notoginseng Relieve Post-c...mentioning
confidence: 99%
“…Panax notoginseng (PN) is not only a Chinese medicine that is used to treat cardiovascular disease (CVD) but is also a dietary supplement. Previous studies have shown that PN exerts many physiological effects; PN is used to treat atherosclerosis [ 1 ], regulate blood sugar [ 2 ], inhibit cancer growth [ 3 ] and metastasis [ 4 , 5 ], protect kidneys [ 6 ], and treat depression [ 7 , 8 ]. Notably, previous studies on the role of PN in alleviating cardiovascular pathology showed that PN can reduce vascular endothelial disorders in C57BL/6 mice fed a high-fat diet by decreasing the phosphorylation of 5’AMP-activated protein kinase (AMPK), the expression of endothelial nitric oxide synthase (eNOS), endoplasmic reticulum stress, and oxidative stress [ 9 ].…”
Section: Introductionmentioning
confidence: 99%